Inflation And Monetary Policy: Bank Indonesia's Role in Suppressing the Inflation Rate of Islamic Economic Objectives - Nugraha, Ahmad Lukman; Janwari, Yadi; Athoillah, Mohamad Anton; Mulyawan, Setia (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This paper aims to define theories of inflation and photograph the response of Muslim scholars to the phenomenon of inflation itself. This paper aims to capture the role and position of Bank Indonesia (BI) as a monetary policy maker in overcoming the rate of inflation. The author uses descriptive qualitative methods of literature study and philosophical normative approaches. The results of this paper analysis state that Bank Indonesia plays an important role in suppressing the rate of inflation. Bank Indonesia plays a role in establishing and implementing monetary policy, regulating and maintaining a smooth payment system, and regulating and supervising banks. Bank Indonesia conducts open market operations in the rupiah money market, including foreign exchange intervention in order to stabilize the rupiah. BI sets the BI rate as the benchmark interest rate. BI has established a mandatory minimum reserve policy for banks. BI conducts comprehensive analysis and studies in assessing the effectiveness of monetary instruments and monetary policy transmission channels, analyzing and reviewing various information variables, conducting discussions with various parties such as business actors, government agencies, banks, and academics, comprehensively identifying factors that cause inflationary pressures, and formulating monetary policy exposure.